2001
DOI: 10.1108/14636646200100004
|View full text |Cite
|
Sign up to set email alerts
|

Discharges from a Learning‐disability Medium Secure Unit: What Happens to Them?

Abstract: Thirty‐five patients who had received at least one year's treatment in a learning‐disability medium secure unit were followed up for a maximum of five years. A good treatment outcome was more common in those with significant learning disability. At the end of follow‐up, 21 subjects (60%) were living in the community with support. The early months after discharge were a peak period for relapse. A very low level of reconviction was found, affecting only one subject. Patients who were older on discharge were less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…Reed et al. (2004) reported these at the point of discharge from a low secure unit, while Halstead et al. (2001) and Alexander et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reed et al. (2004) reported these at the point of discharge from a low secure unit, while Halstead et al. (2001) and Alexander et al.…”
Section: Discussionmentioning
confidence: 96%
“…In the UK, there have been very few studies that reported treatment outcomes from low or medium secure units for offenders with ID. Reed et al (2004) reported these at the point of discharge from a low secure unit, while Halstead et al (2001) and Alexander et al (2006) reported long-term outcomes after discharge from a medium secure unit. Drawing on these three studies, we used median duration of hospital stay and patient care pathway direction as outcome measures.…”
Section: Treatment Outcomesmentioning
confidence: 99%
“…It is far from clear what specialist resources exist for the average ID service as Bailey & Cooper (1997) reported that only 55% of Trusts had access to forensic ID services. There are a few papers published on the therapeutic activities, the general models of treatment and outcomes (Isweran & Bardsley 1987; Day 1988; Halstead et al . 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This study reports on the follow‐up of two cohorts of patients discharged from a medium secure service for people with ID. The first cohort was composed of those discharged between 1987 and 1993 (Halstead et al . 2001 has described this group earlier) and the second was made up of those discharged between 1994 and 2000.…”
Section: Introductionmentioning
confidence: 99%
“…23,[30][31][32][33] It is important to note that many people with intellectual disabilities may not be formally dealt with by criminal justice agencies, and as a consequence, 'formal' arrest and conviction data may not be a valid index of reoffending. Hence, the category of 'reoffending-like behaviour' described in these studies 17,22,29,30 is one which is important because it is likely to have increased validity.…”
Section: Effectivenessmentioning
confidence: 99%